The Globalized Character in the Novel “Women of the Gardens” by Habib Selmi - arar, abouyouneskhalil; Bayou, noura (El Omda in Linguistics and Discourse Analysis, 2022)
Abstract: Globalization has attacked most aspects of life and its activities, and the narrative creativity of the novel is one of them, and this relationship is what lured us to search to explore the manifestation of globalization in the structure of the novel. For procedural reasons, we were satisfied with the character element and not other than the structure of the novel. We chose the novel “Women of the Gardens” by the Tunisian novelist Habib Salmi, and for reasons related to the context in which Tunisian society lives, and for the novel’s place in its cultural movement. In this context, we targeted some personalities suitable for the purpose in their psychological, intellectual and behavioral levels, in order to explore the aesthetic touch that was added to its structure due to the effects of globalization. To achieve this, we followed the targeted personalities in relation to globalization, in terms of values, concepts and manifestations, and we discussed the manifestations of this using the sayings of philosophers and thinkers concerned with globalization, and deconstructors interested in the narrative text.